Relationship between adjunct and full-time faculty teaching at a for-profit university - Strom Kays, Sarah A., author; Kuk, Linda, advisor; Davies, Timothy, advisor (Colorado State University. Libraries, 2009)
This qualitative case study explored the workplace relationships of adjunct and full-time faculty teaching at a for-profit university. The study was conducted at one campus of Segway University. Faculty in this study included men and women and represented different academic departments. All full-time faculty participants had experience teaching as adjunct faculty members. The adjunct faculty in this study all possessed industry-related experience. Findings from this study included an understanding of the perceived relationships and an identification of workplace tensions and competition between the two faculty groups. Administrators and faculty can use the results of this study to improve their workplace relationships by identifying the factors contributing to workplace tension and competition.
Keywords: adjunct faculty; faculty; for-profit university; full-time faculty; higher education teaching; educational leadership; higher education; school faculty; colleges and universities